GENERALIZE THE RANDOMNESS TESTS TO TEST THEDIGITAL SEQUENCES PRODUCED FROM DIGITALSTREAM CIPHER SYSTEMS - Al-Azawi, Faez; Al-Bassam, Sahar; Shamran, Mahmood (Iraqi Journal of Science, 2024)
In this paper, first, the Golomb’s postulates are generalized to construct a goodmathematical base, and then generalize the binary standard randomness tests to besuitable to be applied on digital sequences. This paper includes some tables describethe tests results of the digital sequences generated from some digital generators, likethe Multiplicative Cyclic Group System (MCGS) generator.